Serum Uric Acid to Creatinine Ratio and Risk of Metabolic Syndrome in Saudi Type 2 Diabetic Patients - Al-Daghri, Nasser M. (Sci Rep, 2017)
This study aimed to investigate whether uric acid to creatinine (UA/Cr) ratio is associated with higher risk of metabolic syndrome (MetS) and its components. 332 adult Saudi type 2 diabetes mellitus (T2DM) patients were divided into UA/Cr tertiles. Risk for full MetS was significantly highest in individuals that constitutes the uppermost serum UA/Cr tertile [Odds ratio (OR): 1.80, 95% confidence interval (CI): 1.0–3.3; p < 0.001) after adjustment for age, gender and BMI. Similarly, risk for individual components of MetS like central obesity, hypertriglyceridemia, low HDL-cholesterol and hypertension was significantly highest in this tertile with OR’s of 2.61 (1.2–5.6), 1.42 (0.7–2.3), 1.45 (0.7–2.8) and 1.16 (0.6–2.2) respectively (all p-values < 0.001) after adjustment for age, gender, BMI and other components of MetS. Furthermore, serum UA/Cr levels increased with increasing number of MetS components (mean values of 4.44, 4.49, 4.64, 4.89 and 4.91 respectively for 1,2,3,4 and 5 MetS components, p-values < 0.001 after adjusting for age, gender and BMI). Our data suggest that serum UA/Cr in T2DM patients is strongly associated with full MetS as well as its individual components. These findings are of considerable clinical importance as serum UA/Cr may be used as a marker in the pathogenesis of MetS.